1878 Miss. Laws 175-76 - (:unkn) unknown (My University, 1878)
An Act To Prevent The Carrying Of Concealed Weapons And For Other Purposes, ch. 46, § 2: Prohibited the sale of any Bowie knife, pistol, brass knuckles, slung shot, or other deadly weapon of like kind to any minor or intoxicated person.
Keywords: TRANSFER - DANGEROUS PERSONS; TRANSFER - MINORS